The Influence of Gadget Use on Early Childhood Social Interaction: A Study on the Decline of Interest in Traditional Play - Al Ayyubi, Ibnu Imam; Masfuroh, Ai Sri; Noerzanah, Firda; Nurhikmah; Khan, Anis (Banun: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the influence of gadget use on the social interaction of early childhood and the phenomenon of declining interest in traditional play. A quantitative method with an explanatory research approach was employed. The sampling technique used was probability sampling with a simple random sampling method. Instruments included questionnaires and tests. Data analysis prerequisites were tested using normality (Kolmogorov-Smirnov test) and linearity tests, while hypothesis testing utilized correlation and regression analysis with the assistance of SPSS version 26. The research was conducted at Kober Assa'idiyah, West Bandung Regency, with a population comprising all students and a sample of 20 participants. Results revealed that the data were normally distributed, with Kolmogorov-Smirnov significance values of 0.143 for gadget use and 0.200 for social interaction. Correlation analysis produced a Correlation Coefficient of 0.961, indicating a very strong and significant relationship between gadget use and social interaction. Regression analysis yielded the equation Y=13.506+0.902XY = 13.506 + 0.902XY=13.506+0.902X, meaning an increase of one unit in gadget use correlates with a 0.902 unit increase in social interaction. While gadget use has a significant impact, the study also highlights the importance of managing gadget use to avoid diminishing the quality of social interaction and interest in traditional play. The implications of this research underline the critical role of parents, educators, and policymakers in regulating gadget use to optimally support early childhood social development.